Islamic Modernism in Egypt and its historical background (Journal of Oriental Studies, 2016)
The article is devoted to the study of the historical background of Islamic reform movement in Egypt in the XIX century. Reforming of traditional Islam takes an important place in the history, because this movement plays very important role in the social life of arab countries.The author reveals the ideas of the founder of Islamic modernism Dzhamal al-Din al-Afghani and it’s role in Egyptian society. As well as, investigated the role of the Egyptian intellectual elite in the Islamic reform movement, and provided a brief overview of the ideas of the followers of al-Afghani.
Keywords: colonialism; enlightenment; liberation struggle; Islamic modernism; pan-islamism.